EFEKTIVITAS METODE COMMUNITY LANGUAGE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA ARAB SISWA KELAS V MI IKHLASIYAH PALEMBANG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the effectiveness of the Community Language Learning (CLL) method in improving Arabic language learning outcomes for fifth-grade students at MI Ikhlasiyah Palembang. The problem identified in this research stems from observations indicating that most students consistently scored below the Minimum Competency Criteria (KKM = 65), due to the predominance of rote-memorization-based instruction. This study aims to describe students' Arabic learning outcomes before and after the implementation of the CLL method, as well as to determine the significance of its effectiveness. A quantitative approach with a quasi-experimental design (pretest-posttest control group) was employed, involving 24 students in the control class and 26 in the experimental class. Data were collected through written tests and analyzed using normality (Shapiro-Wilk), homogeneity (Levene's Test), and hypothesis testing (Independent Sample T-Test). The results show that the experimental class's mean score increased from 37.8 (pretest) to 83.4 (posttest), with a gain of 45.6 points, and 100% of students achieved the KKM. The control class improved from 39.8 to 66.6 with a gain of 26.8 points, and only 54.2% achieved the KKM. The T-test yielded t = -3.633 with Sig. (Two-Sided p) < 0.001, indicating that the CLL method significantly and effectively improved Arabic language learning outcomes at MI Ikhlasiyah Palembang.